2019
DOI: 10.3390/e21030285
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Analysis of Temperature Swing Adsorption for CO2 Capture Using the Computational Fluid Dynamics (CFD) Method

Abstract: Carbon capture by adsorption is supposed to be an effective method to reduce CO2 emissions, among which Temperature Swing Adsorption (TSA) can utilize low-grade thermal energy even from renewable energy source. At present, TSA technology still has several challenges to be practical application, such as intensive energy-consumption and low energy-efficiency. Thermodynamics could be a powerful method to explore the energy conversion mechanism of TSA, among which entropy analysis could further provide a clear pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In this technology, an adsorbent agent is used to selectively adsorb and separate CO 2 from the flue gas in a two-step process (Figure 3); CO 2 is initially adsorbed on the surface of the adsorbent agent, which is then regenerated usually via the application of heat (Temperature Swing Adsorption, TSA) or by reducing the pressure (Pressure Swing Adsorption, PSA) [43,44]. For TSA, the energy consumption derives from heating, while for PSA, the energy consumption mainly comes from the compressor system [45]. It is reported that TSA processes offer additional advantages compared to PSA.…”
Section: Adsorptionmentioning
confidence: 99%
“…In this technology, an adsorbent agent is used to selectively adsorb and separate CO 2 from the flue gas in a two-step process (Figure 3); CO 2 is initially adsorbed on the surface of the adsorbent agent, which is then regenerated usually via the application of heat (Temperature Swing Adsorption, TSA) or by reducing the pressure (Pressure Swing Adsorption, PSA) [43,44]. For TSA, the energy consumption derives from heating, while for PSA, the energy consumption mainly comes from the compressor system [45]. It is reported that TSA processes offer additional advantages compared to PSA.…”
Section: Adsorptionmentioning
confidence: 99%